3D CFD Simulations of MOCVD Synthesis System of Titanium Dioxide Nanoparticles - Othman, Siti Hajar; Abdul Rashid, Suraya; Abdullah, Norhafizah; Mohd Ghazi, Tinia Idaty (2013)
This paper presents the 3-dimensional (3D) computational fluid dynamics (CFD) simulation study of metal organic chemical vapor deposition (MOCVD) producing photocatalytic titanium dioxide (TiO2) nanoparticles. It aims to provide better understanding of the MOCVD synthesis system especially of deposition process of TiO2 nanoparticles as well as fluid dynamics inside the reactor. The simulated model predicts temperature, velocity, gas streamline, mass fraction of reactants and products, kinetic rate of reaction, and surface deposition rate profiles. It was found that temperature distribution, flow pattern, and thermophoretic force considerably affected the deposition behavior of TiO2 nanoparticles. Good mixing of nitrogen (N2) carrier gas and oxygen (O2) feed gas is important to ensure uniform deposition and the quality of the nanoparticles produced. Simulation results are verified by experiment where possible due to limited available experimental data. Good agreement between experimental and simulation results supports the reliability of simulation work.